IDENTIFICATION OF ATMOSPHERIC BOUNDARY LAYER THICKNESS USING DOPPLER RADAR WIND PROFILE AT TANGERANG AND ITS SURROUNDING AREA - DEWI (12808028); pembimbing, SARASWATI
The atmospheric boundary layer thickness is one of the important meteorological parameters. Boundary layer thickness can be used to determine the strength of the vertical mixing of pollutants. Furthermore, this parameter is also important in weather and climate models. C-band Doppler radar Serpong which is a cooperation between BPPT and JAMSTEC has a high temporal resolution and wide coverage area. Vertical wind profiles of this radar data is used to identify the top of the Nocturnal Boundary Layer (NBL) and Convective Boundary Layer (CBL). Identification is done by observing the vertical wind shear of the wind profile. NBL top marked by significant wind shear due to the wind speed maximum / Low Level Jet (LLJ) at a height of 1-1.5 km above the ground, while CBL peak marked by increasing wind shear above the mixing layer. By taking a few samples in January 2010 as a representation of wet month and in July 2010 as a representation of dry month, it is indicated that the boundary layer mean thickness in January is less than in July even though the difference is not big enough and diurnal evolution of the boundary layer can be seen. In addition, the differences characteristic of the boundary layer thickness in some areas with different cover can be seen.